2017
DOI: 10.1002/ajpa.23299
|View full text |Cite
|
Sign up to set email alerts
|

A test of the optimal iron hypothesis among breastfeeding Ariaal mothers in northern Kenya

Abstract: We interpret these patterns as tentative support for the optimal iron hypothesis in breastfeeding women in the infectious disease ecology of northern Kenya. Iron deficiency may interact in important ways with other forms of malnutrition that are known to affect immune protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…Milk and blood sample collection methods have been described in depth elsewhere (Fujita, ; Fujita et al, , Fujita & Wander, ). In brief, breast milk collection took place following an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk and blood sample collection methods have been described in depth elsewhere (Fujita, ; Fujita et al, , Fujita & Wander, ). In brief, breast milk collection took place following an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…In the original study, data were collected from consenting mothers under approval of the community chiefs and the institutional review boards of the University of Washington and Kenya Medical Research Institute. Data collection took place during a prolonged drought and food shortage; many mothers were coping with the food shortage by reducing food variety, meal size or the number of meals for their consumption (Apland & Fujita, , , ; Apland, Fujita, & Chang, ; Fujita, ; Fujita, Apland, & Chang, ), and prioritizing their children in allocating limited amount of foods within households (Fujita, ). Our subsequent research found that low BMI (Fujita, ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ), vitamin A deficiency (Fujita, ; Fujita et al, ; Fujita, Lo, & Brindle, ), and iron deficiency (Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita & Wander, ) were prevalent among these mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Low hemoglobin levels (<12 g/dl) defined anemia (Nestel, ). Elevated DBS TfR (>5 mg/L) defined iron deficiency (Fujita & Wander, ; Wander, Shell‐Duncan, & McDade, ). IDA was defined as anemia in presence of iron deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…NIDA was defined as anemia in absence of iron deficiency. Elevated inflammation (probably indicative of acute infection) was identified with elevated blood serum CRP (>5 mg/L; Brindle, Fujita, Shofer, & O'Connor, ; Freedman, ; Fujita & Wander, ; Nakagomi, Freedman, & Geczy, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation